Critical thinking for promoting oral participation through task based learning. (2024)
This research is a proposal aimed at developing critical thinking for promoting oral participation by using the task-based learning approach. The study was conducted in Bogotá D.C. at Liceo Femenino Mercedes Nariño with eleventh-grade students. During the first moments of observation, the students demonstrated good proficiency in English on different tests; however, they showed low participation in English classes. To address that issue, the model of Willis, D. & Willis, J. (2007) was implemented, involving three tasks-based lesson plans designed to develop critical thinking and, consequently, foster oral participation. As a result, the students were able not only to gather information but also to analyze, assess and reconstruct their perspectives. In that way, this approach motivated the students to speak and use the language both spontaneously and in planned scenarios.